Assessment of pruritus in atopic dermatitis: validation of the Severity of Pruritus Scale (SPS). Issue 2 (June 2018) - Yosipovitch, Gil; Simpson, Eric L.; Bushmakin, Andrew G.; Cappelleri, Joseph C.; Luger, Thomas; Ständer, Sonja; Tom, Wynnis L.; Benjamin, Katy; Ports, William C.; Tallman, Anna M.; Tan, Huaming; Gerber, Robert A.
Abstract : Introduction: Pruritus, or itch, is a central feature of atopic dermatitis (AD) and is often cited as the most bothersome symptom. The Severity of Pruritus Scale (SPS) is a 4-point rating scale adapted from the Atopic Dermatitis Severity Index to provide a measure of pruritus severity within a 24-hour recall period. The objective of this analysis was to assess the qualitative and quantitative validity of the SPS in AD. Methods: Content validity of the SPS was evaluated qualitatively in US patients with AD. Psychometric properties of the SPS were evaluated using data from 2 phase 3 trials conducted to investigate crisaborole in mild to moderate AD (study AD-301: NCT02118766; study AD-302: NCT02118792). Results: Fourteen patients were included in the qualitative analysis, considered adequate because of the single-item, single-concept nature of the SPS. Itch was the most prevalent symptom, and the SPS was easily understood and completed in US English (n=9) and US Spanish (n=5). The psychometric analysis used data from 1344 patients. Test-retest reliability analysis identified an intraclass correlation coefficient of 0.54 for a single SPS observation, and at least 0.70 when at least 2 SPS observations were averaged. SPS scores correlated with Investigator's Static Global Assessment (ISGA) scores, measures of quality of life, and 4 of 5 signs of AD (Pearson correlations, ≥0.40 at day 29). The difference in score between the no disease group/clear (ISGA 0) and the severe disease group (ISGA 4) was 0.80. The clinically important difference was estimated to be 0.20 and the clinically important response was estimated to be at least a 0.19-point reduction from baseline. Discussion: The SPS is an appropriate tool to assess itch in patients with AD and is a valid and reliable measure of pruritus severity.